2004
DOI: 10.1038/sj.bjc.6602313
|View full text |Cite
|
Sign up to set email alerts
|

Use of antibiotics and risk of breast cancer: a population-based case–control study

Abstract: We examined the use of antibiotics among 2728 women with a first diagnosis of breast cancer during 1994 -2003, and 27 280 population controls in North Jutland County, Denmark, based on hospital discharge diagnoses, prescription use from 1989 to 2002, and population registry data. We found no increased relative risk of breast cancer associated with use compared with nonuse. The odds ratio for breast cancer associated with more than 10 prescriptions for antibiotics was 1.00 (95% CI 0.86 -1.15). Relative risks we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 10 publications
0
36
1
Order By: Relevance
“…In that study, all classes of antibiotics were associated with increased breast cancer risk and the association persisted after adjustment for factors, such as family history of breast cancer, age at menarche, age at birth of first child, age at menopause, postmenopausal estrogen-replacement therapy, cigarette smoking, alcohol intake, and dietary fat intake (2). Other studies have found either no clear association between breast cancer and antibiotic use (3,4) or a low association (5) between breast cancer and a specific antibiotic, such as flucloxacillin, which is commonly used to treat breast cancer abscess and mastitis (6). Thus, it remains unclear whether antibiotic use is causally related to breast cancer or whether there are common mediators of antibiotic exposure and breast cancer.…”
Section: Introductionmentioning
confidence: 74%
“…In that study, all classes of antibiotics were associated with increased breast cancer risk and the association persisted after adjustment for factors, such as family history of breast cancer, age at menarche, age at birth of first child, age at menopause, postmenopausal estrogen-replacement therapy, cigarette smoking, alcohol intake, and dietary fat intake (2). Other studies have found either no clear association between breast cancer and antibiotic use (3,4) or a low association (5) between breast cancer and a specific antibiotic, such as flucloxacillin, which is commonly used to treat breast cancer abscess and mastitis (6). Thus, it remains unclear whether antibiotic use is causally related to breast cancer or whether there are common mediators of antibiotic exposure and breast cancer.…”
Section: Introductionmentioning
confidence: 74%
“…Similarly, a cohort study in Finland found that antibiotic use for urinary tract infections was associated with increased risk of breast cancer in women under 50 years old, compared to women without such usage [2]. However, two recent case-control studies in the United Kingdom and Denmark found no association between antibiotic use and breast cancer risk [3,4]. Thus, it remains unclear whether antibiotic use is a risk factor for breast cancer, or whether other factors associated with both antibiotic use and breast cancer, such as heightened medical care, are responsible for the observed associations in several studies [1,2].…”
Section: Introductionmentioning
confidence: 98%
“…Based on surveys of diabetic patients between 2000 and 2003, f97% of subscribers have at least partial payment for prescriptions covered by KPMCP and f93% of subscribers fill all of their prescriptions at KPMCP pharmacies. 4 Women ages z20 years with KPMCP drug coverage were identified and followed up starting in August 1994, when implementation of PIMS in all KPMCP pharmacies was completed. Followup began at the time of both joining the program and having drug coverage, if later than August 1994.…”
Section: Methodsmentioning
confidence: 99%